2011
DOI: 10.1590/s1517-83822011000200018
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage, optimal water and organic nutrient supply enhance soil microbial activities during wheat (Triticum Aestivum L.) cultivation

Abstract: The field experiments were conducted on sandy loam soil at New Delhi, during 2007 and to investigate the effect of conservation tillage, irrigation regimes (sub-optimal, optimal and supra-optimal water regimes), and integrated nutrient management (INM) practices on soil biological parameters in wheat cultivation. The conservation tillage soils has shown significant (p<0.05) increase in soil respiration (81.1%), soil microbial biomass carbon (SMBC) (104%) and soil dehydrogenase (DH) (59.2%) compared to the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Further, Saloid-P values were more in surface as compared to subsurface soil perhaps due to slow transformation of soluble forms of P added into sparingly soluble forms with time. This find supported from the findings of Tiwari et al, (2012) and Sharma et al, (2012). Also, Saloid bound P values were lowest among the other fractions and had also been previously reported (Adhikari and Si, 1994;Pati Ram and Mukhopadhyay, 2008) in different soil types.…”
Section: Calcium-psupporting
confidence: 90%
See 1 more Smart Citation
“…Further, Saloid-P values were more in surface as compared to subsurface soil perhaps due to slow transformation of soluble forms of P added into sparingly soluble forms with time. This find supported from the findings of Tiwari et al, (2012) and Sharma et al, (2012). Also, Saloid bound P values were lowest among the other fractions and had also been previously reported (Adhikari and Si, 1994;Pati Ram and Mukhopadhyay, 2008) in different soil types.…”
Section: Calcium-psupporting
confidence: 90%
“…Similar observation have been reported by several authors (Kalaivanan and Sudhir, 2012;Tiwari et al, 2012;Sharma et al, 2012;Dubey et al, 2014;Sarkar et al, 2014;Gopinath et al, 2015;Sanyal et al, 2015).…”
Section: Calcium-psupporting
confidence: 88%
“…Raverkar et al, (2005) studies at a sandy soil site in Rajasthan, we found consistently higher populations of copiotrophic bacteria (that consume high amount of substrate and have higher growth rates) and oligotrophic bacteria ((bacteria that thrive on very low amount of substrate and have slow growth rates) actinomycetes, glomalin, biological activity (dehydrogenase, FDA hydrolysis) and activity of soil enzymes (acid phosphatase, ß-glucosidase) in organic cropping and orchards compared to conventional cropping. on a sandy loam soil in north India on wheat, conservation tillage significantly increased soil respiration (+81.1%), SBMC (+104%) and soil dehydrogenase activity (+59.2%) compared to conventional tillage (Sharma et al, 2011). Acosta-Martínez et al, (2011) reported that an increase in enzyme activities and soil C and N storage under CA practices, particularly under no-till and vetch cover crop that translated in significantly greater TOC and b-glucosidase quality scores.…”
Section: Macroorganismsmentioning
confidence: 97%
“…After 5 years, SOM content, microbial biomass and soil respiration were higher in the two organic plots (with no-till and biomass mulch) as compared to conventional, chemical farming with normal tillage, but highest in the integrated (chemical + plant biomass residue) treatment with normal tillage. In a 2-year field experiment on a sandy loam soil in north India on wheat, conservation tillage significantly increased soil respiration (+81.1%), SBMC (+104%) and soil dehydrogenase activity (+59.2%) compared to conventional tillage (Sharma et al, 2011). Similarly, in a field study on four tillage practices in NE India on ricewheat/mustard/linseed, zero tillage (residue retention and double no-till) recorded higher SMBC, dehydrogenase activity and earthworm population which in turn resulted in good growth and higher yield of all the crops .…”
Section: Macroorganismsmentioning
confidence: 98%
“…Sharma et al (2011) also reported a significant increase in carbon mineralization with the organic amendment. The maximum increase in soil microbial activities were found when sole organic source (farm yard manure (50%) + biofertilizer (25%) + green manure (25%) has been used in combination with the conservation tillage and the optimum water supply.…”
Section: Carbon Mineralization Ratementioning
confidence: 87%